Assessing the impact of environmental laws and technological advancements on carbon dioxide mitigation in China’s mining industry - Dongxiao Xu; Weijun Chen; Yunzhe Chen; Jing Wen (PLoS ONE, 2025)
The present research examines the relationship between China’s mineral extraction-related carbon dioxide (CO2) emissions and factors such as the legislative law, openness, green economic growth, FDI, technology innovation, and green patent from 1989 to 2020. Depending on statistics from the China Statistical Yearbook as well as other global databases, it finds the legislative law and openness contribute to sustainable mineral extracting in China. The efficacies of legislative laws can demonstrate by the substantial decreases in CO2 that occur in response to a one percent rise in these variables. Reducing carbon dioxide emissions is another positive association with the green growth index. The absence of green patents, innovation (patent applications), and foreign direct investment (FDI) unexpectedly reveals consequences on the environment. Improving the long-term sustainability of China’s mineral extracting sector should be a priority for policymakers. To achieve this, we need to reinforce legal frameworks, encourage green economic growth (GEG), integrate foreign direct investment (FDI) with sustainable methods, incentivised green innovations and promote the import of green technology.